Instytucjonalne formy współpracy gospodarczej na pograniczu polsko-niemieckim - przykład TWG SA - Adamczuk, Franciszek (Institutional Forms of the Economic Cooperation on the Polish-German Border on the Example of TWG SA, 2006)
The aim of this article is to show the role of TWG SA in the cooperation between Poland and Germany, especially in the border regions. All issues were discussed on the new background - Poland as a member of the European Union. The last part presents conclusions and proposal that night be useful for the further activities of TWG SA.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 116-123